Parathyroid Autotransplantation During thyroid Surgery. Where we are? A Systematic Review on Indications and Results - Olga Iorio; Vincenzo Petrozza; Antonietta De Gori; Marco Bononi; Natale Porta; Giorgio De Toma; Giuseppe Cavallaro (Journal of Investigative Surgery, 2019)
Introduction: Hypoparathyroidism still represents an important concern in thyroid surgery. Careful dissection with identification and preservation of parathyroid glands in situ remains the best way to maintain gland vitality and avoid post-operative failure. Nevertheless, parathyroid glands are still inadvertently removed in up to 11% of cases. Parathyroid autotransplantation may represent the only way to restore parathyroid gland functionality in case of inadvertent removal or devascularization during thyroid surgery. Despite this, there is still no agreement on the effectiveness of this procedure. The present systematic review is focused on the mainly debated matters regarding the procedure, indications, technique and results. Methods: This review has been carried out according to PRISMA statement and checklist. The research item was: (((parathyroid autotransplantation[Title]) OR parathyroid reimplantation[Title]) NOT hyperparathyroidism[Title]) AND english[Language]. Results: A total of 31 studies have been found according to limitations already described, reporting from 4 to 890 procedures, with a total amount of 4088 PA. Among these studies, there are only 7 prospective case-series evaluations, 2 prospective randomized trials, while the other 22 studies are retrospective evaluations. The main concerns are: when and how to perform autotransplantation; in which anatomical site; which result to be expected, and how to manage and control the graft. Conslusions: Parathyroid autotransplantatin is an important tool to avoid or minimize the risk for hypoparathyroidism following thyroid surgery in selected cases. Parathormone assay can help the surgeon to determine when reimplantation is indicated or not. Further studies could theoretically give definitive results.